Crack path effects on vibration characteristics in structural beams and plates - Alshammari, Yousef Lafi A.; Khan, Muhammad; He, Feiyang; Doğanay Kati, Hilal; Buhari, Jamilu (British Institute of Non-Destructive Testing (BINDT), 2025)
Accurately assessing and forecasting damage development is essential for maintaining safety, enhancing maintenance efficiency, and prolonging the service life of components in sectors like aerospace, automotive and civil infrastructure. This study examines the impact of crack characteristics — including path, length, and orientation — on the vibration characteristics of metallic and polymeric structures using both numerical and experimental methods. Using aluminium (AL) cantilever beams, numerical simulations were employed to determine the natural frequencies and associated amplitude using 13 different crack propagation paths. Results show that changes in crack orientation in the beam's depth significantly affected frequency and amplitude trends. Complementing this, experimental modal analysis (EMA) and the half-power bandwidth method were conducted on 10 crack paths on AL and 3D-printed ABS plates to examine how surface crack length and orientation influence damping ratios. Findings indicated that longer cracks increased damping due to reduced stiffness and microslip, resulting in more energy dissipation, while orientation, especially along the primary deformation axis, had a more substantial effect. ABS plates exhibited higher damping than aluminium due to their viscoelastic properties. Overall, the study highlights the critical role of crack paths in dynamic behaviour, which enhances damage identification and advanced structural health monitoring.
Keywords: 3403 Macromolecular and Materials Chemistry; 40 Engineering; 34 Chemical Sciences